Manufacturing method for Ni-base superalloy
Patent Information
- Application Number
- JP2024538484
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-09-19
- Filing Date
- 2024-03-08
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2044-03-08
AI Technical Summary
【0011】 本発明によれば、効率よく扇状γ’相の析出領域を低減させることが可能である。
Smart Images

Figure 0007632767000003 
Figure 0007632767000004 
Figure 0007632767000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a Ni-base superalloy. [Background technology]
[0002] In order to improve the efficiency of aircraft engines and the power generation efficiency of gas turbines, it is effective to operate the turbines at high temperatures. To achieve this, it is important to increase the service temperature of each turbine component. For components that require a service temperature of 600°C or higher, gamma prime (γ') phase precipitation strengthened Ni-base superalloys are often used. The γ' phase is an L12 structure intermetallic compound, typically Ni3Al, and it is known that the precipitation strengthening effect is further enhanced by dissolving elements such as Ti, Nb, and Ta in this. γ' phase precipitation strengthened Ni-base superalloys are mainly composed of two phases, the γ phase, which becomes the matrix, and the γ' phase, which becomes the precipitation phase. When the amount of Ti or Nb added is increased, intermetallic compounds such as eta phase (Ni3Ti, etc.) and delta phase (Ni3Nb, etc.) may precipitate as a third phase. In addition, C and B are often added mainly for the purpose of strengthening the grain boundaries of the matrix, and trace amounts of carbides and borides may crystallize or precipitate.
[0003] In order to increase the high-temperature strength of Ni-base superalloys, it is effective to increase the amount of Al, Ti, Nb, and Ta added, which form and strengthen the γ' phase, as mentioned above. This increases the amount of γ' phase precipitated and also strengthens the γ' phase itself. An example of a high-strength Ni-base superalloy is Udimet 720Li (UDIMET is a registered trademark of Special Metals Corporation).
[0004] Ni-base superalloys containing large amounts of Ti, Nb, and Ta have high strength, but even after hot working, microsegregation tends to remain, making it difficult to obtain a homogeneous microstructure. The main cause of microsegregation is said to be the uneven distribution of additive elements in the alloy to the solid or liquid phase during the solidification process. In particular, additive elements such as Ti, Nb, and Ta, which contribute to increasing the amount of γ' phase precipitation and strengthening, tend to concentrate in the liquid phase during the solidification process of the ingot, so microsegregation occurs inside the ingot after solidification is complete. This microsegregation is promoted as the solidification rate slows, so it becomes more noticeable as the ingot size increases. In order to reduce this microsegregation, a heat treatment process called homogenization is generally introduced as the next process. Homogenization is often applied to ingots, but it can also be applied to billets as an intermediate process in hot working.
[0005] Homogenization is often performed at a temperature equal to or higher than the solid solution temperature of a second phase such as the γ' phase and lower than the melting point, but the appropriate conditions for homogenization, such as the required heating temperature, heating holding time, and cooling rate, are not necessarily determined because they vary greatly depending on not only the chemical composition but also the solidification rate of the ingot. In Ni-based superalloys with a large amount of γ' precipitation, the γ' phase precipitates during the cooling process after the homogenization treatment, so the cooling rate has a significant effect on the subsequent hot workability. The faster the cooling after the homogenization treatment, the finer the γ' phase precipitates, but if hot working is performed in this state, the fine γ' phase is likely to hinder the movement of dislocations. As a result, the deformation resistance of the workpiece becomes significantly high and recrystallization is difficult to occur, making it more likely to cause hot cracks. As a means of solving this problem, for example, as disclosed in Patent Document 1, it is possible to coarsen the γ' phase by slowing the cooling rate after heating, thereby improving hot workability.
[0006] Ni-based superalloys with a large amount of γ' precipitates after homogenization, such as Udimet 720Li, can be hot worked in the two-phase region of γ and γ' phases, and recrystallized while the undissolved γ' phase acts as pinning particles at the γ grain boundaries, to obtain a uniform and fine microstructure. However, the uniformity of the microstructure after hot working is strongly affected by the distribution of γ' phase, which acts as pinning particles. This is because the more non-uniform the γ' phase distribution is, the coarser the γ phase grains are in the regions with a wide distance between γ' phase particles, and the finer they are in the regions with a narrow distance between γ' phase particles. Therefore, in order to obtain a uniform microstructure after hot working, it is necessary to uniformly disperse the γ' phase particles. If the microstructure is non-uniform, fatigue fracture may easily occur from partially coarse grains, which is undesirable in practice. Therefore, it is desirable that the distribution of grains in the microstructure is as uniform as possible.
[0007] When Ni-base superalloys are cooled, the γ' phase generally precipitates in the form of spheres or cubes within the grains. However, it is known that when Ni-base superalloys with a large amount of γ' precipitation are heated to near or above the solid solution temperature of the γ' phase and then cooled at a slow cooling rate, a fan-shaped γ' phase (also called fan-type γ' phase) precipitates. This fan-shaped γ' phase mainly precipitates from the grain boundaries and grows with the grain boundary migration. The order of precipitation during cooling is usually such that the fan-shaped γ' phase precipitates first, followed by the spherical or cubic intragranular γ' phase. The temperature range in which the fan-shaped γ' phase precipitates is not fixed, but it is particularly noticeable in the temperature range from the γ' phase solid solution temperature of each alloy to about 50°C below the solid solution temperature of the γ' phase. Therefore, the slower the cooling rate in this temperature range, the larger the precipitation region of the fan-shaped γ' phase becomes, and conversely, the narrower the precipitation region of the intragranular γ' phase becomes. This fan-shaped γ' phase is coarse and has an elongated shape with a large aspect ratio compared to the γ' phase precipitated within the grains. In other words, the fan-shaped γ' phase is a γ' phase precipitated with a non-uniform distribution. However, as mentioned above, in order to homogenize the microstructure after hot working in Ni-base superalloys with a large amount of γ' precipitation, it is better for the size of the γ' phase to be uniform. Therefore, if a large amount of fan-shaped γ' phase precipitates during cooling after the homogenization treatment, it becomes difficult to obtain a uniform microstructure after hot working. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] International Publication No. 2014 / 157144 Brochure Summary of the Invention [Problem to be solved by the invention]
[0009] When a Ni-based superalloy with a large amount of γ' precipitates is subjected to a homogenization treatment of heating and cooling, a large amount of fan-shaped γ' phase precipitates during cooling. This fan-shaped γ' phase precipitates mainly from the grain boundaries, but it is characterized by being coarse, having a large aspect ratio, and being non-uniformly distributed compared to the γ' phase precipitated within the grains. Ni-based superalloys with a large amount of γ' precipitates, such as Udimet 720Li, can obtain a uniform and fine microstructure by hot working in the two-phase region of γ and γ' phases and causing recrystallization while the undissolved γ' phase acts as a pinning particle for the γ phase grain boundaries. However, if the precipitation region of the fan-shaped γ' phase is wide after the homogenization treatment, the size and distribution of the γ' phase as a pinning particle becomes non-uniform, and the size of the recrystallized grains generated during the subsequent hot working process also becomes non-uniform, which causes a problem that it is difficult to obtain a uniform microstructure. In view of this, an object of the present invention is to provide a method for reducing the precipitation region of the sectorial γ' phase during homogenization treatment of a Ni-base superalloy having a large amount of γ' precipitates. [Means for solving the problem]
[0010] That is, the present invention relates to a composition, by mass%, of C: 0.001-0.100%, Al: 1.0-5.0%, Ti: 3.5-7.0%, Cr: 8-20%, Co: 0-40%, Mo: 0-7.0%, W: 0-5.0%, Ta: 0-6.0%, Nb: 0-6.0%, B: 0.001-0.080%, Zr: 0-0.100%, Mg: 0-0.05%, Fe: 0-5.0%, and the balance being Ni and unavoidable impurities, and the solid solution temperature of the γ' phase is 1080° C. or higher. The manufacturing method of the above Ni-base superalloy includes at least a step of heat treating a material having the above composition, the heat treatment step including a step of heating at a temperature range of 1170°C to 1280°C for 45 hours or more, and a cooling step in which the average cooling rate in the temperature range from the solid solution temperature of the γ' phase to the solid solution temperature of the γ' phase minus 50°C satisfies [average cooling rate (°C / hour)]≧10 and [average cooling rate (°C / hour)]≧200-2.0×[holding time (hours)]. The heating step is preferably performed for 45 hours or more and 300 hours or less. Alternatively, the average cooling rate is preferably 800 ≧ [average cooling rate (°C / hour)] ≧ 10. Alternatively, the heating step is preferably performed for 60 hours or more and the average cooling rate is preferably 100 ≧ [average cooling rate (°C / hour)] ≧ 10. Effect of the Invention
[0011] According to the present invention, it is possible to efficiently reduce the area where the sector-shaped γ' phase precipitates. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a diagram showing the metal microstructure of a Ni-based superalloy produced in an embodiment. [Diagram 2] FIG. 2 is a diagram showing the metal microstructure of a Ni-based superalloy produced in an embodiment. [Diagram 3] FIG. 2 is a diagram showing the metal microstructure of a Ni-based superalloy produced in an embodiment. [Figure 4] FIG. 2 is a diagram showing the metal microstructure of a Ni-based superalloy produced in an embodiment. [Diagram 5]FIG. 2 is a diagram showing the metal microstructure of a Ni-based superalloy produced in an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The reasons for limiting the alloy composition ranges specified in the present invention will be described below. The composition values shown below are in mass %. <C:0.001~0.100%> C has the effect of increasing the strength of the grain boundaries, so it is necessary to add 0.001% or more. On the other hand, if C is contained in excess, coarse carbides are formed and become harmful, so the upper limit is set to 0.100%. It is preferably 0.005% or more, more preferably 0.01% or more. It is also preferably 0.06% or less, more preferably 0.03% or less.
[0014] <Al:1.0~5.0%> Al is an essential element that forms the γ' phase, which is a strengthening phase, and improves high-temperature strength. Since the present invention is directed to alloys with a large amount of γ' phase precipitation, it is necessary to add at least 1.0%. On the other hand, excessive addition of Al excessively increases the solid solution temperature of the γ' phase, so the upper limit is set to 5.0%. It is preferably 1.5% or more, more preferably 1.8% or more. It is also preferably 4.0% or less, more preferably 3.0% or less.
[0015] <Ti:3.5~7.0%> Ti is an element that substitutes for the Al site of the γ' phase, strengthens the γ' phase with solid solution, and increases the amount of γ' phase precipitated. To be covered by the present invention, a minimum of 3.5% is necessary. On the other hand, excessive addition makes the γ' phase unstable and causes the eta phase to precipitate excessively, so the upper limit is set at 7.0%. It is preferably 4.6% or more, and more preferably 5.8% or more. It is also preferably 6.8% or less, and more preferably 6.6% or less.
[0016] <Cr:8~20%> Cr is an element that improves oxidation resistance and corrosion resistance. A Cr content of 8% or more is necessary because a deficiency in Cr leads to cracking due to oxidation. On the other hand, an excessive Cr content forms embrittled phases such as sigma phases, so the upper limit is set to 20%. It is preferably 10% or more, more preferably 12% or more. It is also preferably 17% or less, more preferably 15% or less.
[0017] <Co:0~40%> Co contributes to the stability of the γ' phase, so it may be added as necessary. On the other hand, if Co is added in excess, embrittled phases such as sigma phases tend to precipitate, so the upper limit is set to 40%. It is preferably 35% or less, more preferably 30% or less, and even more preferably 28% or less. When Co is added, it is preferably 5% or more, more preferably 15% or more, and even more preferably 20% or more.
[0018] <Mo:0~7.0%> Mo contributes to solid solution strengthening of the matrix and has the effect of improving high-temperature strength and creep deformation resistance, so it may be added as necessary. On the other hand, excessive addition of Mo excessively lowers the melting point, so the upper limit is set to 7.0%. It is preferably 5.0% or less, more preferably 3.5% or less, and even more preferably 3.0% or less. When added, it is preferably 0.5% or more, more preferably 1.0% or more, and even more preferably 2.0% or more.
[0019] <W:0~5.0%> W, like Mo, is an element that contributes to solid solution strengthening of the matrix, so it may be added as necessary. However, since W is a heavy element, it is difficult for diffusion to occur in the alloy, so the upper limit is set to 5.0%. It is preferably 4.0% or less, more preferably 2.5% or less, and even more preferably 1.6% or less. Furthermore, when W is added, it is preferably 0.5% or more, more preferably 0.8% or more, and even more preferably 1.0% or more.
[0020] <Ta:0~6.0%> Ta, like Ti, is an element that substitutes for the Al site of the γ' phase to solid-solution strengthen the γ' phase and increase the high-temperature strength. Therefore, it may be added as necessary to obtain a high-strength alloy. However, excessive addition makes the γ' phase unstable and forms a large amount of eta phase and delta phase, so the upper limit is set to 6.0%. It is preferably 5.0% or less, more preferably 4.0% or less, and even more preferably 3.0% or less. When added, it is preferably 0.5% or more, more preferably 1.0% or more, and even more preferably 1.5% or more.
[0021] <Nb:0~6.0%> Like Ti and Ta, Nb is an element that substitutes for the Al site of the γ' phase to solid-solution strengthen the γ' phase and increase the high-temperature strength. Therefore, Nb may be added as necessary to obtain a high-strength alloy. However, excessive addition makes the γ' phase unstable and forms a large amount of eta phase and delta phase, so the upper limit is set to 6.0%. It is preferably 5.0% or less, more preferably 4.0% or less, and even more preferably 3.0% or less. When added, it is preferably 0.5% or more, more preferably 1.0% or more, and even more preferably 1.5% or more.
[0022] <B:0.001~0.080%> Since B is an important element for improving grain boundary strength and improving creep strength and high temperature ductility, 0.001% or more is necessary. On the other hand, excessive addition of B excessively lowers the melting point, so the upper limit is set to 0.080%. It is preferably 0.003% or more, more preferably 0.006% or more, and even more preferably 0.010% or more. It is also preferably 0.060% or less, more preferably 0.040% or less, and even more preferably 0.030% or less.
[0023] <Zr:0~0.100%> Zr is said to have the effect of improving the grain boundary strength like B, but it is not essential. Similar to B, when the addition amount of Zr increases, it causes a decrease in the melting point, so the upper limit is set to 0.100%. Preferably it is 0.080% or less, more preferably 0.060% or less, and even more preferably 0.050% or less. Also, when adding, preferably it is 0.005% or more, more preferably 0.007% or more, and even more preferably 0.010% or more.
[0024] <Mg: 0 to 0.05%> Mg has the effect of improving the grain boundary strength by fixing the inevitable impurity S that causes grain boundary embrittlement as a sulfide, so it may be added as necessary. However, when the addition amount increases, excess Mg forms harmful intermetallic compounds, so the upper limit is set to 0.05%. Preferably it is 0.01% or less, more preferably 0.005% or less, and even more preferably 0.001% or less. Also, when adding, preferably it is 0.0003% or more, more preferably 0.0005% or more.
[0025] <Fe: 0 to 5.0%> Fe is an inexpensive element, and it is possible to replace a part of Ni with Fe to reduce the raw material cost of the hot-worked material. Therefore, it may be contained as necessary. However, excessive addition of Fe promotes the precipitation of the sigma phase, so the upper limit is 5.0%. Preferably it is 4.0% or less, more preferably 1.5% or less, and even more preferably 1.0% or less. Also, when containing, preferably it is 0.05% or more, more preferably 0.1% or more, and even more preferably 0.3% or more.
[0026] <Ni: balance> The balance consists of Ni and inevitable impurities. Here, examples of the inevitable impurity elements include P, S, O, N, Pb, As, etc., and it is preferable that the total amount of these does not exceed 0.05%.
[0027] The reasons for the limitation regarding the solution temperature of the γ' phase defined in the present invention will be explained below. <Solution temperature of γ' phase> The Ni-base superalloys to which the present invention is directed have a γ'-phase solid solution temperature of 1080° C. or higher. This is because the growth rate of the sector-shaped γ' phase is rapid in the high temperature range, and therefore, in alloys having a γ'-phase solid solution temperature of less than 1080° C., a microstructure with fewer sector-shaped γ' phase precipitation regions can be obtained without applying the present invention.
[0028] Next, the reasons for limiting the heating temperature and holding time during the homogenization treatment in the heat treatment step according to the present invention will be explained below. <Homogenization temperature> The heating temperature during the homogenization treatment specified in the present invention must be in the range of 1170°C to 1280°C. If the temperature is less than 1170°C, the diffusion in the Ni-base superalloy is insufficient, and the effect of the homogenization treatment cannot be obtained. On the other hand, if the temperature exceeds 1280°C, local melting in the Ni-base superalloy becomes significant, and the effect of the homogenization treatment cannot be obtained sufficiently. It can also be said that the heating temperature during the homogenization treatment is a temperature exceeding the solid solution temperature of the γ' phase.
[0029] <Holding time during homogenization treatment> The holding time during homogenization treatment specified in the present invention is the total holding time during heating at the heating temperature range of 1170°C to 1280°C. Therefore, it does not include the heating time in the temperature range below 1170°C. This is because, in order to obtain the effects of the present invention, it is necessary to heat and hold the Ni-base superalloy in a temperature range where sufficient diffusion occurs in the Ni-base superalloy. However, a preliminary heat treatment in a temperature range below 1170°C is effective in avoiding local melting in the solidified structure, so it may be applied as necessary.
[0030] The holding time during the homogenization treatment specified in the present invention must be 45 hours or more. It is preferably 60 hours or more, and more preferably 85 hours or more. This heating and holding does not necessarily have to be continuous, and may be divided. For example, the ingot may be subjected to a total of two homogenization treatments. Also, for example, after the ingot is subjected to one homogenization treatment, it may be subjected to a certain amount of hot working to form a billet, and this billet may be subjected to another homogenization treatment. The reason for specifying the heating holding time is from the viewpoint of both reducing microsegregation and reducing the fan-shaped γ' phase precipitation region. The Ni-base superalloy targeted by the present invention contains a large amount of additive elements such as Ti, so that not only microsegregation but also fan-shaped γ' phase is likely to precipitate, but by setting the holding time to the specified time or more, it is possible to simultaneously reduce both. The reason why not only microsegregation but also fan-shaped γ' phase precipitation can be suppressed is considered to be as follows, although the present invention is not limited to this principle. When the holding time during homogenization is longer, microsegregation is reduced and the concentration gradient of solute elements such as Al, Ti, Nb, and Ta is reduced. The smaller the concentration gradient of these elements, the more uniform the solid solution temperature of the local γ' phase in the microstructure is. Then, when cooling from the solid solution temperature of the γ' phase or higher, the area where the solute elements are concentrated, i.e., the area where the precipitation start temperature of the fan-shaped γ' phase is locally high, is reduced, so it is considered possible to delay the precipitation and growth. Note that the longer the holding time during homogenization, the higher the effect, so there is no upper limit specified, but it is preferably 300 hours or less from the viewpoint of working time.
[0031] <Cooling rate after homogenization treatment> The cooling rate after homogenization treatment specified in the present invention is the average cooling rate in the temperature range of "50°C" from the γ' phase solid solution temperature to the γ' phase solid solution temperature minus 50°C. By increasing the cooling rate in this temperature range, it is possible to reduce the precipitation region of the fan-shaped γ' phase. The average cooling rate specified in the present invention must satisfy [average cooling rate (°C / hour)] ≥ 200-2.0 x [holding time (hours)]. This means that the longer the holding time, the slower the cooling rate is allowed. The present invention is not limited to the weight of the applied material, but is particularly effective in large ingots weighing several hundred kg or more. Large ingots have a slow solidification rate, so microsegregation is significant, and fan-shaped γ' phases tend to precipitate during cooling after homogenization treatment. However, if the cooling rate after homogenization treatment is excessively increased in an attempt to avoid the precipitation of the fan-shaped γ' phase, the surface temperature of the ingot will preferentially decrease, making it more likely to cause cooling cracks. Since the cracking sensitivity increases as the ingot becomes larger, it is insufficient in practice to only specify the cooling rate after homogenization. In the present invention, the minimum required average cooling rate is obtained from the holding time, so that efficient homogenization is possible in that the precipitation of the sector-shaped γ' phase can be reduced while avoiding cooling cracks. In addition to the above formula, the average cooling rate must be at least 10°C / hour or more. It is preferably 25°C / hour or more, and more preferably 40°C / hour or more. Although the upper limit of the cooling rate is not specified, it is preferably 800°C / hour or less, and more preferably 500°C / hour or less, from the viewpoint of cooling cracks and subsequent hot workability. And, by ensuring a long holding time (for example, by ensuring 60 hours or more), the precipitation region of the sector-shaped γ' phase can be reduced even if the average cooling rate is slowed to 100°C / hour or less. It is preferable that the average cooling rate is maintained beyond the "50°C" temperature range from the γ' phase solid solution temperature to the γ' phase solid solution temperature minus 50°C, and further up to 900°C. EXAMPLES
[0032] In order to confirm the effect of the present invention, a homogenization experiment was carried out according to the following procedure. First, an electrode of Ni-based superalloy was prepared in a vacuum induction furnace (VIM), which was then refined and melted by electroslag remelting (ESR), and further refined and melted by vacuum arc remelting (VAR) to obtain a Ni-based superalloy VAR ingot weighing about 1.0 to 1.5 tons and measuring approximately 450 mm in diameter. The chemical composition of this material is shown in Table 1. The γ'-phase solid solution temperature of an alloy with this chemical composition is approximately 1165°C.
[0033] [Table 1]
[0034] Next, the top side of this VAR ingot was cut, and a small piece material of about 10 mm x 15 mm x 20 mm was cut out from the position of 1 / 4 diameter from the surface. The top side of the VAR ingot was used because the microsegregation at this part was remarkable and it can be said to be a suitable material for confirming the effect of the present invention. The cut small piece material was sealed in a stainless steel can and then subjected to the homogenization treatment shown in Table 2. An electric furnace was used for these homogenization treatments. In the homogenization treatment, the small piece material was first preheated at a specified temperature and holding time, and then the temperature was raised to the heating temperature for the homogenization treatment. Then, in the cooling process after holding at this heating temperature for a specified time, the cooling rate listed in Table 2 is the average cooling rate in the "temperature range from 1165 ° C to 1115 ° C". Table 2 also shows the value A calculated by 200-2.0 x [holding time (hours)]. Among them, No. 4 to No. 11 satisfy the holding time and average cooling rate specified by the present invention. The cooling rate after the homogenization treatment was maintained up to at least 900°C, after which the material was either continued to be cooled to room temperature in the furnace at the same cooling rate setting, or, after confirming that the temperature had fallen to 900°C or below, removed from the furnace and cooled to room temperature.
[0035] [Table 2]
[0036] After homogenization, the small pieces of material were cut so that the longitudinal direction of the VAR ingot became the observation surface. The observation surface of the small pieces of material was mirror-polished, and then electrolytically etched in a 10% oxalic acid solution to facilitate observation of the γ' phase. An optical microscope was used for microstructural observation. Microstructural photographs of No. 1 to No. 11 in Table 2 are shown in the order of Figure 1(A), (B), (C), Figure 2(D), (E), Figure 3(F), (G), Figure 4(H), (I), and Figure 5(J), (K), respectively.
[0037] First, it was found from Figures 1(A), (B), and (C) that the microstructures of No. 1, No. 2, and No. 3 had widespread precipitation of fan-shaped γ' phases at and near the grain boundaries. From Table 2, it can be seen that the value A of the homogenization treatment conditions for these samples was greater than the cooling rate, and therefore these samples are outside the scope of the present invention. Next, in No. 6 and No. 7, which had the same cooling rate as No. 1 at 60°C / h, but the holding time was extended to 120 hours and 200 hours, respectively, it was confirmed from Figures 3(F) and (G) that the precipitation region of the sector-shaped γ' phase was significantly reduced compared to No. 1. In addition, in No. 8, which had the same cooling rate as No. 2 and No. 3 at 25°C / h, but the holding time was extended to 300 hours, it was confirmed from Figure 4(H) that the precipitation region of the sector-shaped γ' phase was significantly reduced. From the above, it was confirmed that the homogenization treatment with a long holding time has the effect of significantly reducing the precipitation region of the sector-shaped γ' phase, as proposed by the present invention.
[0038] In addition, it was confirmed from FIG. 2(E) that No. 5, which had the same holding time as No. 2 and a cooling rate of 100°C / h, had a smaller precipitation region of the sector-shaped γ' phase. In addition, it was confirmed from FIG. 4(I) that No. 9, which had the same holding time as No. 3 and a cooling rate of 80°C / h, also had a smaller precipitation region of the sector-shaped γ' phase. In addition, No. 4 had the shortest holding time of 48 hours in Table 2, but it was confirmed from FIG. 2(D) that the cooling rate was 200°C / h faster than the others, resulting in a smaller precipitation region of the sector-shaped γ' phase. From the above, it was confirmed that, as proposed by the present invention, increasing the cooling rate after the homogenization treatment has the effect of significantly reducing the precipitation region of the sector-shaped γ' phase.
[0039] In addition, it was confirmed from Figures 5(J) and 5(K) that the microstructures of No. 10 and No. 11, in which the preheating temperature and the subsequent heating rate were changed, also had small areas of precipitation of the fan-shaped γ' phase.
Claims
1. A method for producing a Ni-base superalloy having a composition, in mass%, of C: 0.001-0.100%, Al: 1.0-5.0%, Ti: 3.5-7.0%, Cr: 8-20%, Co: 0-40%, Mo: 0-7.0%, W: 0-5.0%, Ta: 0-6.0%, Nb: 0-6.0%, B: 0.001-0.080%, Zr: 0-0.100%, Mg: 0-0.05%, Fe: 0-5.0%, and the balance being Ni and unavoidable impurities, and having a solid solution temperature of the γ' phase of 1080° C. or higher, comprising the steps of: A method for producing a Ni-base superalloy, comprising at least a step of heat treating an ingot or a billet material obtained by hot working the ingot, the heat treatment step comprising: a step of heating at a temperature range of 1170°C to 1280°C for 45 hours or more; and a cooling step in which an average cooling rate in the temperature range from the solid solution temperature of the γ' phase to the solid solution temperature of the γ' phase minus 50°C satisfies 500 ≧ [average cooling rate (°C / hour)] ≧ 10 and [average cooling rate (°C / hour)] ≧ 200 - 2.0 × [holding time (hours)].
2. The method for producing a Ni-base superalloy according to claim 1, wherein the heating step comprises heating for 45 hours or more and 300 hours or less.
3. 2. The method for producing a Ni-base superalloy according to claim 1, wherein the heating step comprises heating for 60 hours or more, and the average cooling rate is 100≧[average cooling rate (°C / hour)]≧10.
Citation Information
Patent Citations
Ni-BASED ALLOY REPAIRING MEMBER AND MANUFACTURING METHOD OF THE REPAIRING MEMBER
JP2021172852A
Thermomechanical processing for fatigue-resistant nickel based superalloys
US5061324A
METHOD FOR MANUFACTURING Ni-BASED SUPER-HEAT-RESISTANT ALLOY
WO2016129485A1
Ni-BASED SUPER HEAT-RESISTANT ALLOY AND TURBINE DISK USING SAME
WO2016152985A1
Ni-based alloy member manufacturing method
WO2023243146A1